Hadith #2292 - Sunan al-Nasa'i - al-'Awwam bin Hushab العوام بن حوشب بن يزيد; Hameed bin Musa'da bin al-Mubarak حميد بن مسعدة بن المبارك; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan al-Nasa'i)
the Prophet went out in Ramadan and fasted until he came to Qudaid, then a cup of milk was brought to him and he drank and broke his fast; he and his Companions.
Grade:

Hadith #5209 - Sunan al-Nasa'i - al-'Awwam bin Hushab العوام بن حوشب بن يزيد; Anas ibn Malik; Azhar bin Rashid al-Hwzny أزهر بن راشد الهوزني; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Mjahd bin Musa مجاهد بن موسى (Sunan al-Nasa'i)
“The ring of the Prophet was made of silver and its stone (Fass) was made of silver too.”
Grade:

Hadith #5694 - Sunan al-Nasa'i - al-'Awwam bin Hushab العوام بن حوشب بن يزيد; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Ziyad bin Ayoub - Dulwiyya زياد بن أيوب بن زياد دلويه (Sunan al-Nasa'i)
“Khamr was forbidden in and of itself in small or large amounts, as was every kind of intoxicating drink.”
Grade:

Hadith #3090 - Sunan Abi Dawud - Abu Barda bin Abi Musa al-Asha'ari أبو بردة / الحارث بن أبي موسى الأشعري; Abu Musa al-Asha'ari; al-'Awwam bin Hushab العوام بن حوشب بن يزيد; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Ibrahim bin 'Abdur Rahman al-Saksaki إبراهيم بن عبد الرحمن السكسكي; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان (Sunan Abi Dawud)
on his father’s authority said his grandfather reported: He was a Companion of the Messenger of Allah (ﷺ) said: I heard the Messenger of Allah (ﷺ) say: When Allah has previously decreed for a servant a rank which he has not attained by his action, He afflicts him in his body, or his property or his children. Abu Dawud said: Ibn Nufail added in his version: “He then enables him to endure that.” The agreed version goes: “So that He may bring him to the rank previously decreed from him
Grade: Sahih

Hadith #4645 - Sunan Abi Dawud - al-'Awwam bin Hushab العوام بن حوشب بن يزيد; Amr bin 'Awn/'Auf bin Aws; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Sa'id bin Jmhan سعيد بن جمهان; Safinah (Sunan Abi Dawud)
I prayed the Friday prayer with al-Hajjaj and he addressed. He then transmitted the tradition of Abu Bakr b. ‘Ayyash. He said in it: Hear and obey the caliph of Allah and his select ‘Abd al-Malik bin Marwan. He then transmitted the rest of the tradition, and said: If I seized Rabi’ah for Mudar. But he did not mention the story of the clients (i.e. non Arabs).
Grade: Sahih

Hadith #1059 - Jami' al-Tirmidhi - Abu 'Ubaida bin 'Abdullah bin Mas'ud أبو عبيدة بن عبد الله بن مسعود; al-'Awwam bin Hushab العوام بن حوشب بن يزيد; ibn Mas'ud; Ishaq bin Yusuf bin Mrdas إسحاق بن يوسف بن مرداس; Nasr bin 'Ali bin Nasr bin 'Ali (Jami' al-Tirmidhi)
“I arrived in Al-Madinah and while I was sitting with Umar bin Al-Khattab they passed by with a funeral, over (a person) whom they were praising with good. Umar said: ‘Granted.’ I said to Umar: ‘What is granted?’ He said: ‘I said as the Messenger of Allah said: “There is no Muslim about whom three bear witness, except that he is granted Paradise.” He said: “And two (as well).” He said: ‘We did not ask the Messenger of Allah about one.'”
Grade:

Hadith #3610 - Jami' al-Tirmidhi - al-'Awwam bin Hushab العوام بن حوشب بن يزيد; Anas ibn Malik; Muhammad bin Bashar Bindar محمد بن بشار بندار; Sulaiman bin Abi Sulaiman سليمان بن أبي سليمان; Yazid bin Harun يزيد بن هارون (Jami' al-Tirmidhi)
“O Allah, give me pleasure in my hearing and my sight, and make it the inheritor from me, and aid me against whoever oppresses me, and take vengeance from him for me (Allāhumma matti`nī bisam`ī wa baṣarī waj`alhumal-wāritha minnī, wanṣurnī `alā man yaẓlimunī, wa khudh minhu bitha’rī)”
Grade:

Hadith #108 - Sunan Ibn Majah - Abdullah bin Khrash bin Hwshb عبد الله بن خراش; al-'Awwam bin Hushab العوام بن حوشب بن يزيد; ibn Abbas; Mujahid bin Jabir مجاهد بن جبر (Sunan Ibn Majah)
“The Messenger of Allah forbade men to perform ablution with the water left over by a woman, and women to perform ablution with water left over by a man, however both (spouses) may start to perform their ablutions at the same time.” Abu `Abdullah Ibn Majah said: “The first (narration) is correct, and the second (narration) is Wahm (an error).” Another chain with similar wording.
Grade:

Hadith #1674 - Sunan Ibn Majah - Abu 'Ubaidah ibn al-Jarrah; al-'Awwam bin Hushab العوام بن حوشب بن يزيد; ibn Mas'ud; Ishaq bin Yusuf bin Mrdas إسحاق بن يوسف بن مرداس; Nasr bin 'Ali bin Nasr bin 'Ali (Sunan Ibn Majah)
that the Messenger of Allah said: “Breastfeeding once or twice, or suckling once or twice, does not make (marriage) unlawful.”
Grade:

Hadith #2564 - Sunan Ibn Majah - Abdullah bin Sa'id bin Abi Hind عبد الله بن سعيد بن أبي هند; al-'Awwam bin Hushab العوام بن حوشب بن يزيد; ibn Abbas; Mujahid bin Jabir مجاهد بن جبر (Sunan Ibn Majah)
“I asked the Messenger of Allah (ﷺ) about the food of the Christians and he said: ‘Do not have any doubt about food, (thereby) following the way of the Christians in that.’”
Grade:

Hadith #4215 - Sunan Ibn Majah - al-'Awwam bin Hushab العوام بن حوشب بن يزيد; ibn Mas'ud; Jabla bin Sahaym جبلة بن سحيم; Muhammad bin Bashar Bindar محمد بن بشار بندار; Yazid bin Harun يزيد بن هارون (Sunan Ibn Majah)
“We used to come across groups of Quraish who would be talking, but they would stop talking (when we approached). We mentioned that to the Messenger of Allah and he said: ‘What is the matter with people who talk, then when they see a man from my family they stop talking? By Allah, faith will not enter a person’s heart until he loves them for the sake of Allah and because of their closeness to me.'”
Grade: